Enhancing the competitiveness of agricultural commodity chains in Nigeria: Identifying opportunities with cassava, rice, and maize using a Policy Analysis Matrix (PAM) framework - Liverpool-Tasie, Lenis Saweda O.; Ayoola, Gbolagade B.; Oyeleke, Razaq O. (International Food Policy Research Institute, 2009)
Since registering a disappointing growth of 1.2 percent in 2002, Nigeria's economic performance has rebounded, averaging growth at 7.3 percent between then and 2007. However, the pressing challenge for the nation lies in maintaining and improving current economic growth indicators and translating these recent gains into an improved standard of living for the majority of its citizens. Poverty within Nigeria remains staggeringly high with over 50 percent and 70 percent of its general and rural population respectively, living on less than US1$ a day. Similarly, though Nigeria is often cited as one of the largest oil exporting countries, agriculture still remains the main employer of over 70 percent of the country’s labor force and accounts for about 31 percent of the nation’s GDP. Consequently, the importance of this sector in national development and poverty alleviation cannot be overemphasized.